Analytical methodology optimization to estimate the content of non-flavonoid phenolic compounds in Argentine propolis extracts. (July 2014) - Isla, María Inés; Salas, Ana; Danert, Fatima C.; Zampini, Iris Catiana; Ordoñez, Roxana Mabel
Abstract Context: Traditionally, the content of total phenolics (flavonoid phenolics (FP) and non-flavonoid phenolics (NFP)) and flavonoids (flavone/flavonol and flavonone/dihydroflavonol) in propolis has been determined by different methodologies. Until now, the percentage of total phenolic (TP) compounds that corresponds to FP and NFP, expressed in the same units by a spectrophotometric method, has not been determined. Objective: The current study proposes a quick and simple methodology that separates FP and NFP in propolis samples and determines TP, FP, and NFP by the same method. Materials and methods: Propolis samples from five Argentine provinces (Tucumán, Santiago del Estero, Salta, Misiones, and Jujuy) were used. Extraction of TP from the propolis samples was carried out by maceration with 80% ethanol and quantified by Folin–Ciocalteu reagent (FC-R). Then, FP was precipitated with formaldehyde in acid medium. After centrifugation, NFP were determined in the supernatant using FC-R. FP content was calculated as the difference between the content of TP and NFP. The method was also validated using commercial flavonoids and chalcones. Results: FP recovery in all experiments was between 85.95% and 98.29%. Propolis from Tucumán had significantly higher amounts of total phenols than propolis from other provinces. SE5 showed higher content of FP (81.52%) followed by SA1 (74.75%). The propolis from TUC4, SA4, SE3, and MI showed the lowest FP content and highest content of NFP. Conclusions: This method provides a simple, reliable, and specific spectrophotometric assay to estimate the content of NFP, FP, and TP in propolis samples.